Metabolizable Ultrathin Bi2Se3 Nanosheets in Imaging‐Guided Photothermal Therapy. Issue 30 (22nd June 2016) - Xie, Hanhan; Li, Zhibin; Sun, Zhengbo; Shao, Jundong; Yu, Xue‐Feng; Guo, Zhinan; Wang, Jiahong; Xiao, Quanlan; Wang, Huaiyu; Wang, Qu‐Quan; Zhang, Han; Chu, Paul K.
Abstract : Poly(vinylpyrrolidone)‐encapsulated Bi2 Se3 nanosheets with a thickness of 1.7 nm and diameter of 31.4 nm are prepared by a solution method. Possessing an extinction coefficient of 11.5 L g −1 cm −1 at 808 nm, the ultrathin Bi2 Se3 nanosheets boast a high photothermal conversion efficiency of 34.6% and excellent photoacoustic performance. After systemic administration, the Bi2 Se3 nanosheets with the proper size and surface properties accumulate passively in tumors enabling efficient photoacoustic imaging of the entire tumors to facilitate photothermal cancer therapy. In vivo biodistribution studies reveal that they are expelled from the body efficiently after 30 d. The ultrathin Bi2 Se3 nanosheets have large clinical potential as metabolizable near‐infrared‐triggered theranostic agents. Abstract : Ultrathin Bi2 Se3 nanosheets with a thickness of 1.7 nm and diameter of 31.4 nm are successfully synthesized by a "green" solution‐based method. The ultrathin Bi2 Se3 nanosheets deliver excellent photothermal and photoacoustic performance and are well metabolized. These attractive properties render the ultrathin Bi2 Se3 nanosheets promising as a near‐infrared‐triggered theranostic agents in cancer therapies.